The Overcoming Oneself (ke ji) in the Analects of Confucius: the End of Personality or its Foundation? - Silius, Vytis (Acta Orientalia Vilnensia, 2004)
The paper contains an analysis of the conception of personality concentrated in the ideal of exemplary person (jun zi) in classical Confucianism as it is shown in The Analects of Confucius. An attempt is made to discover what unique features, according to Confucius, are characteristic of such an exemplary person. So the meaning and significance of the two interrelated ethical categories of classical Confucianism, ren and li, is shown. In the second part of the paper, author tries to expose how, in accordance with The Analects, the ideal of jun zi may be reached. Thereto author analyzes the meaning of ke ji in The Analects and offers a new translation of the term, claiming that his approach contributes to a better understanding of the conception of personality in classical Confucianism.